Residential status and health in middle and late life: a population-based study with new data from Spain - Miguel Requena; David Reher (BMJ Open)
Objectives To address how different residential situations impact the likelihood of death among mature adults and elderly persons.Design Population-based study with administrative data linked to census data.Setting Spain.Participants Spanish population alive on 1 January 2012, observed between 1 January 2012 and 31 December 2012. A 10% random sample of the Spanish population, including 2 054 427 person years and 28 736 deaths, is used.Main outcome measure Registered deaths in the 2012 Spanish vital statistics.Methods Using a new data set based on linked administrative registers, we estimate unadjusted and adjusted mortality rates by coresidential situation. Differential mortality is measured by rate ratios (RR) estimated with Poisson regression. Cause of death data are used to explore the mechanisms involved in excess mortality by residential status.Results Compared with men 45–54 living with partners, the risk of death is much higher for those without partners living with others (RR 2.0, 95% CI 1.7 to 2.4) or for those living alone (RR 1.9, 95% CI 1.5 to 2.4). After 84, excess mortality among men living with others persists (RR 1.4, 95% CI 1.3 to 1.5), but disappears for those living alone (RR 1.0, 95% CI 0.9 to 1.1). Both among women 45–64 living with others but without partner (RR 1.8, 95% CI 1.5 to 2.3) and among those living alone (RR 2.2, 95% CI 1.5 to 3.1) the pattern is similar to men. At higher ages, however, excess mortality for women living alone decreases (RR 1.2, 95% CI 1.1 to 1.2), though it persists for women living with others (RR 1.9, 95% CI 1.7 to 2.0).Conclusions These findings indicate direct effects of living arrangements on mortality and health-related selection effects influencing residential choices. These effects may be partially affected by age and prevailing societal and cultural contexts.